Global links and local bonds. The role of ownership and size in productivity growth - Erol Taymaz; Ebru Voyvoda; Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2010)
This paper examines direct and indirect contributions of foreign firms and small and medium-sized enterprises (SMEs) to aggregate productivity growth. We focus our attention on foreign firms and small firms for three reasons. First, industrial policy in almost all countries is oriented towards supporting SMEs and attracting foreign investment. Second, these two categories of firms contribute to micro-heterogeneity in all industries. Third, the recent industrial dynamics literature on foreign investment and small firms emphasizes the potential benefits of foreign firms and SMEs in generating new technologies, and creating new jobs. Using the data for Turkish manufacturing plants, we estimate production functions for all ISIC 4-digit level industries for the 1983-2001 period. We decompose productivity growth into its components (structural change, entry and exit, technical change, efficiency change, and scale effects) by firm ownership and size. The decomposition analysis by firm ownership and size allows us to understand the sources of productivity contributions by foreign firms and small firms.
Keywords: D24; L25; L60; 330; productivity dynamics; decomposition; foreign direct investment; small and medium sized enterprises; Eigentümerstruktur; Betriebsgröße; Produktivität; Klein- und Mittelunternehmen; Türkei